OPDA-Ile - a new JA-Ile-independent signal? - Wasternack, Claus; Hause, Bettina (Plant signaling & behavior, 2016)
Expression takes place for most of the jasmonic acid (JA)-induced genes in a COI1-dependent manner via perception of its conjugate JA-Ile in the SCFCOI1-JAZ co-receptor complex. There are, however, numerous genes and processes, which are preferentially induced COI1-independently by the precursor of JA, 12-oxo-phytodienoic acid (OPDA). After recent identification of the Ile-conjugate of OPDA, OPDA-Ile, biological activity of this compound could be unequivocally proven in terms of gene expression. Any interference of OPDA, JA, or JA-Ile in OPDA-Ile-induced gene expression could be excluded by using different genetic background. The data suggest individual signaling properties of OPDA-Ile. Future studies for analysis of an SCFCOI1-JAZ co-receptor-independent route of signaling are proposed.
Keywords: signální transdukce; Signal Transduction; proteiny huseníčku; SCFCOI1-JAZ coreceptor complex; Cyclopentanes; Fatty Acids, Unsaturated; 12-oxo-phytodienoic acid (OPDA); OPDA-Ile-induced gene expression; nenasycené mastné kyseliny; Plant Growth Regulators; jasmonic acid (JA); JA-Ile perception; Arabidopsis Proteins; cyklopentany; jasmonoyl-isoleucine (JA-Ile); Arabidopsis; oxylipiny; regulátory růstu rostlin; Oxylipins; isoleucin; Isoleucine